Spatial Variation of Shallow Soil Bearing Capacity Using SPT Data and MATLAB Analysis - Al-Mamoori, Sohaib K.; Karkush, Mahdi; Al-Baghdadi, Waseem; Al-Rumaithi, Ayad (Civil Engineering Journal, 2025)
The current research examines the spatial distribution of shallow bearing capacity in Al-Najaf City through the use of Standard Penetration Test (SPT) data supplemented with advanced computational tools in MATLAB. A high-quality geotechnical survey of 464 boreholes was carried out, with drilling performed at depths ranging from 18 m to 35 m below the current ground surface. To assess the shallow foundations, the top 12 m of the soil profile was analyzed. To measure in-situ soil resistance, SPT measurements were taken at specified depth intervals in every borehole. The raw SPT N-values were adjusted for overburden pressure, an energy-correction parameter, and groundwater effects; other minor adjustments were considered negligible based on their minimal impact on the final dataset. These corrected N-values formed the basis for calculating both ultimate and allowable bearing capacities using empirically developed correlations. MATLAB surface-interpolation procedures were used to generate georeferenced thematic maps that depict the lateral variation of bearing capacity within the 0–12 m depth interval. The resulting spatial analysis shows a significant increase in the bearing capacity of the northern and western regions of Al-Najaf, correlating with increases in urbanization and infrastructure density. The predictive geotechnical maps developed in this study can be considered a highly robust, cost-effective, and timely tool for initial subsurface engineering surveys to guide sustainable city development, infrastructure design, and optimization of foundation engineering.